Mr. Ferris and his wheel - Davis, Kathryn Gibbs (Houghton Mifflin Harcourt Publishing Company, 2014)
Examines how the engineer George Ferris invented and constructed the amusement park ride that bears his name for the 1893 Chicago World's Fair.